Dietary patterns are associated with dietary recommendations but have limited relationship to BMI in the Communities Advancing the Studies of Tribal Nations Across the Lifespan (CoASTAL) cohort - Fialkowski, M.; McCrory, M.; Roberts, S.; Tracy, J.; Grattan, L.; Boushey, Carol (Cambridge University Press, 2012)
Objective Traditional food systems in indigenous groups have historically had health-promoting benefits. The objectives of the present study were to determine if a traditional dietary pattern of Pacific Northwest Tribal Nations (PNwT) could be derived using reduced rank regression and if the pattern would be associated with lower BMI and current Dietary Reference Intakes. Design The baseline data from the Communities Advancing the Studies of Tribal Nations Across the Lifespan (CoASTAL) cohort were used to derive dietary patterns for the total sample and those with plausibly reported energy intakes. Setting Pacific Northwest Coast of Washington State, USA. Subjects Adult PNwT members of the CoASTAL cohort with laboratory-measured weight and height and up to 4 d of dietary records (n 418). Results A traditional dietary pattern did not evolve from the analysis. Moderate consumption of a sweet drinks dietary pattern was associated with lower BMI while higher consumption of a vegetarian-based dietary pattern was associated with higher BMI. The highest consumers of the vegetarian-based dietary pattern were almost six times more likely to meet the recommendations for dietary fibre. Conclusions Distinct dietary patterns were found. Further exploration is needed to confirm whether the lack of finding a traditional pattern is due to methodology or the loss of a traditional dietary pattern among this population. Longitudinal assessment of the CoASTAL cohort's dietary patterns needs to continue.